Determinación de la calidad de agua mediante parámetros físicos, químicos y microbiológicos en la microcuenca Sicalpa, cantón Colta - Cumbal Imbaquingo, Freddy Marcelo (2023)
The objective of the thesis was to determine the water quality through the use of physical, chemical and microbiological parameters in the Sicalpa river micro-basin, Colta canton. The study was carried out in the dry season in the months of June to September; Starting with a geospatial analysis to determine the morphometry. For the collection of water samples, 24 points were selected, which were georeferenced using a GPS. Once the samples were obtained, they were transferred to the UNACH environmental services laboratory to carry out the respective analysis of: Temperature, Hydrogen Potential, Turbidity, Total Dissolved Solids, Biochemical Oxygen Demand, Dissolved Oxygen, Phosphates, Nitrates and Fecal Coliforms. The results indicate a small, flat micro-basin, with accidental portions in the Návag, where its streams are drained over long periods of time. The physical, chemical, and microbiological parameters show important variations between the upper and lower micro-basins, which had high rates in the samplings and reported an ICA of 67.90, 68.01, 68.07 and 68.42, which indicates regular quality water. The variabilities in the results show the influence of anthropic activity on the deterioration of water quality in our study area.